Freshwater Microbial Eukaryotic Core Communities, Open-Water and Under-Ice Specialists in Southern Victoria Island Lakes (Ekaluktutiak, NU, Canada) - Potvin, Marianne; Rautio, Milla; Lovejoy, Connie (Frontiers in Microbiology, 2022)
Across much of the Arctic, lakes and ponds dominate the landscape, starting in late September the lakes are ice covered, with ice persisting well into June or early July. In summer the lakes are highly productive supporting waterfowl and fish populations. However, little is known about the diversity and ecology of microscopic life in the lakes that influence biogeochemical cycles and contribute to ecosystem services. Even less is known about prevalence of species that are characteristic of the seasons or whether some species persist year-round under both ice cover and summer open water conditions. To begin to address these knowledge gaps, we sampled 10 morphometrically diverse lakes in the region of Ekaluktutiak, (Cambridge Bay) on southern Victoria Island (Nunavut, Canada). We focused on Greiner Lake, lakes connected to it, isolated ponds and two nearby larger lakes outside the Greiner watershed. The largest lakes sampled were Tahiryuaq, (Ferguson Lake) and nearby Spawning Lake, which support commercial sea-run Arctic Char (Salvenlinus alpinus) fisheries. Samples for nucleic acids were collected from the lakes along with limnological metadata. The microbial eukaryotes were identified by way of high throughput amplicon sequencing targeting the V4 region of 18S rRNA gene. Ciliates, dinoflagellates, chrysophytes and cryptophytes dominated the lake assemblages. A Bray-Curtis dissimilarity matrix separated communities into under-ice and open-water clusters, with additional separation by superficial lake area. In all, 133 operational taxonomic units (OTUs) occurred either in all under-ice or all open-water samples and were considered “core” microbial species or ecotypes. These were further characterized as seasonal indicators. Ten of the OTUs were characteristic of all lakes and all seasons sampled. Eight of these were cryptophytes, suggesting diverse functional capacity within the lineage. The core open-water indicators were mostly chrysophytes, with a few ciliates and uncharacterized Cercozoa. Suggesting that summer communities are mixotrophic with contributions by heterotrophic taxa. Core under-ice indicators included a dozen ciliates along with chrysophytes, cryptomonads and dinoflagellates, indicating a more heterotrophic community augmented by mixotrophic taxa in winter.